CO2 Uptake Model of Biomass Silica Foamed Concrete - Lee, Yee Loon; Koh, Heng Boon; Abdul Karim, Ahmad Tarmizi; Wimala, Mia; Ng, C. (International Journal of Integrated Engineering, 2010)
The cement industry contributes about 5% to global anthropogenic CO2 emissions. CO2 is emitted from the calcination process of limestone, from combustion of fuels in the kiln, as well as from power generation. A model of CO2 uptake by biomass silica foamed concrete is proposed as a potential mitigation strategy against CO2-emission. The key parameters in the cement production process are defined and the total CO2 emissions are reviewed. A comparison between CO2 emission and CO2 uptake by carbonation is made. The forecasting of CO2 uptake by carbonation is modeled with the use of Microsoft Excel. The CO2 emission mitigation options are discussed based on the modeling on CO2 uptake by biomass silica foamed concrete. The proposed foamed concrete absorbs CO2 42.7% faster than the normal Portland cement concrete, with a regression accuracy of 0.98. Successful deployment could contribute towards sustainable development while benefiting from the carbon credits.